Benchmarking Family Therapy for Adolescent Behavior Problems in Usual Care: Fidelity, Outcomes, and Therapist Performance Differences - Hogue, Aaron (Adm Policy Ment Health, 2017)
This study evaluated whether community therapists delivering family therapy for adolescent behavior problems in usual care achieved performance benchmarks established in controlled trials for treatment fidelity and outcomes, with particular focus on individual differences in therapist performance. The study contained N = 38 adolescents (50% male; mean age 15 years) whose self-reported race/ethnicity was Hispanic (74%), African American (11%), multiracial (11%), and other (4%). Clients were treated by 13 therapists in one community mental health clinic that delivered family therapy as the routine standard of care. Therapists provided self-report data on adherence to core family therapy techniques; these scores were inflation-adjusted based on concordance with observer reports. Results showed that community therapists surpassed the fidelity benchmark for core family therapy techniques established by research therapists during a controlled trial. Regarding change in client functioning at six-month follow-up, community therapists were equivalent to the benchmark for internalizing symptoms and superior for externalizing symptoms and delinquent acts. Community therapists also demonstrated a high degree of performance uniformity: Each one approximated the fidelity benchmark, and only two produced relatively weak outcomes on any of the client change indicators. Caveats for interpreting therapist performance data, given the small sample size, are described. Recommendations are made for developing therapist-report fidelity measures and utilizing statistical process control methods to diagnose therapist differences and enhance quality assurance procedures.